Poverty and Lack of Knowledge Cause Negligence on Female Elders Lived in Extended Familie - Setho Hadisuyatmana; Muhammad Rully Maulana; Makhfudli Makhfudli (Jurnal Ners, 2016)
Introduction: Elder neglect remains as unreported case that involved old women in Ampenan West Nusa Tenggara. Despite the paucity of evidence to report the significance, an earlier pilot study showed that elders who lived with their family in Ampenan were found dirty, skin dry, and malnourished. The purpose of this study was to explore the correlating factors to the unreported cases of neglect among these elders. Method: This study was a cross sectional conducted using analytic descriptive approach. Thirty-four extended families lived with female elders in the working area of Puskesmas Ampenan were purposively involved as participants to this study. Family’s awareness of abuse was collected using a questionnaire developed based on Elder Abuse Instrument component checklist and the suspicion to neglect among the elders were collected using the 13-item checklist from Elder Abuse Instrument. The data were then analyzed using Spearman’s rho (α ≤ 0,05). Result:  The results show that family’s lack of knowledge has a strong correlation with elder neglect (p= 0,000 with r= 0,643). Discussion: The analysis to this finding suggests that not only were the families lack of knowledge, but they were also being burden by the poor economic situation that trigger the unnecessary neglect to their female elders. These results abridge the paucity of evidence to explain the correlating factors with the incidence of elder abuse in eastern Indonesia. Further research is necessary to explain the size and the impact of neglect toward the elders. It is suggested that local department of health, Puskesmas and health professionals to educate the community as the first step to improve the elders’ quality of life and promote healthy ageing.